Biocompatibility of glass-ionomer cements using mouse lymphoma cells in vitro - Ribeiro, D. A.; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Blackwell Publishing, 2006)
Glass-ionomer cements are widely used in dentistry as restorative materials and adhesives for composite restorations. A number of genotoxicity studies have been conducted using these materials with results conflicting so far. Thus, the approach was aimed to look at the genotoxic and cytotoxic potential of three different glass-ionomer cements available commercially (Ketac Cem, Ketac Molar and Vitrebond) by the single cell gel (comet) assay and trypan blue exclusion test, respectively. For this, such materials were exposed to mouse lymphoma cells in vitro for 1 h at 37 degrees C. Data were assessed by Kruskall-Wallis non-parametric test. The results showed that all powders assayed did not show genotoxic effects. on the other hand, the liquid from Vitrebond at 0.1% dilution caused an increase of DNA injury. Significant statistically differences (P < 0.05) in cytotoxicity provoked by all powders tested were observed for exposure at 1000 mu g mL(-1) concentration and 100 mu g mL(-1) for Ketac Molar. With respect to liquids of glass-ionomer cements evaluated, the major toxic effect on cell viability was produced at 1%, beginning at the dilution of 0.5% for Vitrebond. Taken together, these results support the notion that some components of glass-ionomer cements show both genotoxic and cytotoxic effects in higher concentrations.
Keywords: cytotoxicity; genotoxicity; glass-ionomer cements; mouse lymphoma cells